SS433's jet trace from ALMA imaging and global jet watch spectroscopy: evidence for post-launch particle acceleration - Blundell, K; Laing, R; Lee, S; Richards, A (American Astronomical Society, 2018)
We present a comparison of Doppler-shifted Hα line emission observed by the Global Jet Watch from freshly launched jet ejecta at the nucleus of the Galactic microquasar SS433 with subsequent Atacama Large Millimeter/submillimeter Array (ALMA) imaging at mm-wavelengths of the same jet ejecta. There is a remarkable similarity between the transversely resolved synchrotron emission and the prediction of the jet trace from optical spectroscopy: this is an a priori prediction and not an a posteriori fit, confirming the ballistic nature of the jet propagation. The mm-wavelength of the ALMA polarimetry is sufficiently short that the Faraday rotation is negligible and therefore that the observed ${\boldsymbol{E}}$-vector directions are accurately orthogonal to the projected local magnetic field. Close to the nucleus, the ${\boldsymbol{B}}$-field vectors are perpendicular to the direction of propagation. Further out from the nucleus, the ${\boldsymbol{B}}$-field vectors that are coincident with the jet instead become parallel to the ridge line; this occurs at a distance where the jet bolides are expected to expand into one another. X-ray variability has also been observed at this location; this has a natural explanation if shocks from the expanding and colliding bolides cause particle acceleration. In regions distinctly separate from the jet ridge line, the fractional polarization approaches the theoretical maximum for synchrotron emission.